A review of Copelatus Erichson, 1832 of Mainland China, with description of ten new species from the japonicus complex (Coleoptera: Dytiscidae: Copelatinae) - Jiang, Zhuo-Yin; Zhao, Shuang; Yang, Zhen-Yu; Jia, Feng-Long; Hájek, Jiří (Zootaxa, 2022)
The species of the genus Copelatus Erichson, 1832 from China Mainland are reviewed. 22 species are recorded in total. Ten new species: C. dentatipenis sp. nov. (Fujian, Hunan, Jiangxi), C. diversistriatus sp. nov. (Yunnan; Laos, Myanmar, Thailand), C. felicis sp. nov. (Yunnan), C. miaowangi sp. nov. (Guizhou), C. mopanshanensis sp. nov. (Yunnan), C. nanlingensis sp. nov. (Guangdong), C. puzhelongi sp. nov. (Yunnan; Laos, Vietnam), C. rosulae sp. nov. (Yunnan), C. tengchongensis sp. nov. (Yunnan), and C. xiniudong sp. nov. (Guizhou) are described. Copelatus chinensis Régimbart, 1899 is reinstituted as a valid species with Copelatus collocallosus Falkenström, 1932 and C. collocallosus Falkenström, 1933 as its junior subjective synonyms. One species from Hongkong remains unidentified since it is so far known only from a limited number of females. Additional records are provided for the known species; three species: C. bacchusi Wewalka, 1981, C. malaisei Guignot, 1954 and C. parallelus Zimmermann, 1920 are recorded from China for the first time. Copelatus takakurai Satô, 1985 is withdrawn from the Chinese fauna. All species are diagnosed, and their habitus and male genitalia are illustrated. An updated identification key to Chinese Copelatus is provided.